Never touch a spider! - Rosie Greening (Tennessee; Make Believe Ideas Ltd, 2020)
Meet the creepy-crawlies in this fun rhyme, perfect for adults and children to enjoy together. Have fun touching the bumpy bugs ... if you dare!
Keywords: Board books